Indigenous landscapes and Spanish missions : new perspectives from archaeology and ethnohistory - Panich, Lee M., 1978-; Schneider, Tsim D., 1979- (Archaeology of colonialism in native North America., 2014)
"Spanish missions in North America were once viewed as confining and stagnant communities, with native peoples on the margins of the colonial enterprise. Recent archaeological and ethnohistorical research challenges that notion. Indigenous Landscapes and Spanish Missions considers how native peoples actively incorporated the mission system into their own dynamic existence. The book, written by diverse scholars and edited by Lee M. Panich and Tsim D. Schneider, covers missions in the Spanish borderlands from California to Texas to Georgia. Offering thoughtful arguments and innovative perspectives, the editors organized the book around three interrelated themes. The first section explores power, politics, and belief, recognizing that Spanish missions were established within Indigenous landscapes with preexisting tensions, alliances, and belief systems. The second part, addressing missions from the perspective of Indigenous inhabitants, focuses on their social, economic, and historical connections to the surrounding landscapes. The final section considers the varied connections between mission communities and the world beyond the mission walls, including examinations of how mission neophytes, missionaries, and colonial elites vied for land and natural resources. Indigenous Landscapes and Spanish Missions offers a holistic view on the consequences of missionization and the active negotiation of missions by Indigenous peoples, revealing cross-cutting perspectives into the complex and contested histories of the Spanish borderlands. This volume challenges readers to examine deeply the ways in which native peoples negotiated colonialism not just inside the missions themselves but also within broader Indigenous landscapes. This book will be of interest to archaeologists, historians, tribal scholars, and anyone interested in Indigenous encounters with colonial institutions"--